The Use of Duolingo Application as A Learning Medium for Students’ Pronunciation - Syair, Siti Nurazizah; Baa, Sultan; Talib, Ahmad (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2024)
This research aimed to find out how students’ use and to assess their perception of the Duolingo application as a medium for learning pronunciation. This current research used a descriptive qualitative method with subjects of this research were two students of English Education at Universitas Negeri Makassar and random sampling was used in which the subjects that were being randomized had been using the Duolingo application for a long time. The instruments used in this research were observation by observing students using the Duolingo application using an observation checklist, and interviews using semi-structured interviews, namely interviews using interview guides originating from the subject concerned. The results of the research concluded that: The use of Duolingo application consists of; students chose the level on the application, students do pronunciation exercises in the application, students studied vowels and consonants features in the application, students get feedback from the application, students have and use several additional features contained in the application. Furthermore, students positive perception of the Duolingo application; in cognitive aspects, students perceive that the Duolingo application is an online learning tool that can be used as a learning medium for learning pronunciation, in affective aspects students feel helped and made it easier when learning pronunciation using this application because there are interesting features that can increase students' excitement and make it easy for students to understand the instructions, in conative aspect, students using Duolingo application with follow the instructions provided and focus on each exercise and material contained in the application. While using this application, students can feel changes in their pronunciation. The changes in pronunciation experienced by students do not take long because they often use it in everyday life. The Duolingo application can be used every day, wherever and whenever because it is online-based and also free. Therefore, the Duolingo application can be used as a learning medium for learning pronunciation.